Culture, conflict and cooperation: Irish dairying before the great war - O'Rourke, K (Blackwell Publishing, 2007)
A recent literature argues that ‘hierarchical religions’ such as Catholicism hamper the formation of trust, thus reducing the propensity to cooperate and damaging economic performance. This article looks for a link between Catholicism and the propensity to cooperate in the pre-1914 Irish dairy industry. Although the propensity to cooperate was higher in Denmark than in Ireland, and in Ulster than elsewhere in Ireland, Catholicism did not make cooperation more difficult in Ireland. Political conflict over land reforms and constitutional matters was to blame, not religion. Denmark's homogeneity, not its Protestantism, led to the success of cooperation there.